Design of Smart Home System Using Arduino - S. Abdul Malik, K. Valibabu, C. Padma (Mathematical Statistician and Engineering Applications, 2022)
The rapid growth of technology has drastically changed the living standards of modern society. Seeing the increasing number of electronic devices being made in a household, an automated home control system has become an increasing useful feature. Current systems, however, have problems with complexity, high costs, non-open sources and multiple incompatible standards; resulting in the limited venture of the home automation into the homes of the rich or hobbyists. The main objective of this work is to develop a home automation system using an Arduino board with Bluetooth being remotely controlled by any Android OS smart phone. As technology is advancing so houses are also getting smarter. Modern houses are gradually shifting from conventional switches to centralized control system, involving remote controlled switches. Presently, conventional wall switches located in different parts of the house makes it difficult for the user to go near them to operate. Even more it becomes more difficult for the elderly or physically handicapped people to do so. Remote controlled home automation system provides a most modern solution with smart phones. HC-06 Arduino Bluetooth Module and Arduino Uno, LDR and DHT11 temperature and humidity sensors, which are used as light sensors, are integrated to provide reactions according to light, temperature and humidity conditions in the environment.